Savoring The Success: Cultivating Innovation And Creativity For Indonesian Culinary MSMEs Growth - Mulyono, Herry; Rolando, Benediktus (PT. Maju Malaqbi Makkarana, 2024)
The culinary industry in Indonesia has witnessed a surge in the growth of Micro, Small, and Medium Enterprises in recent years. These enterprises, known as culinary MSMEs, have played a pivotal role in the country's economic development. To remain competitive in the dynamic market, these MSMEs need to embrace innovative and creative strategies that can drive their growth and sustainability. This paper aims to provide a comprehensive understanding of the innovation and creativity strategies employed by Indonesian culinary MSMEs and identify the key factors that contribute to their success. The study found that culinary MSMEs in Indonesia can adopt a range of innovative and creative strategies to enhance their competitiveness. These may entail developing novel and distinctive menu offerings, implementing efficient production processes, leveraging digital technologies for marketing and customer engagement, and fostering an organizational culture that promotes innovation. By adopting a customer-centric approach and remaining responsive to evolving market trends, these enterprises can distinguish themselves from competitors and maintain a leading position in the industry. A systematic review of the existing literature also reveals that culinary MSMEs in Indonesia face various challenges, including financial constraints, lack of human resources, and limited access to information and technology. To address these challenges, collaboration with external parties, such as the government, research institutions, and universities, can be a crucial step in enhancing the innovation capabilities of these enterprises.